Characterization of Macrophage Polarization States Using Combined Measurement of 2-Deoxyglucose and Glutamine Accumulation: Implications for Imaging of Atherosclerosis. Issue 10 (October 2017) - Tavakoli, Sina; Downs, Kevin; Short, John D.; Nguyen, Huynh Nga; Lai, Yanlai; Jerabek, Paul A.; Goins, Beth; Toczek, Jakub; Sadeghi, Mehran M.; Asmis, Reto
Abstract : Objective—: Despite the early promising results of 18 F-fluorodeoxyglucose positron emission tomography for assessment of vessel wall inflammation, its accuracy in prospective identification of vulnerable plaques has remained limited. Additionally, previous studies have indicated that 18 F-fluorodeoxyglucose uptake alone may not allow for accurate identification of specific macrophage activation states. We aimed to determine whether combined measurement of glucose and glutamine accumulation—the 2 most important bioenergetic substrates for macrophages—improves the distinction of macrophage inflammatory states and can be utilized to image atherosclerosis. Approach and Results—: Murine peritoneal macrophages (MΦ) were activated ex vivo into proinflammatory states with either lipopolysaccharide (MΦLPS ) or interferon-γ+tumor necrosis factor-α (MΦIFN-γ+TNF-α ). An alternative polarization phenotype was induced with interleukin-4 (MΦIL-4 ). The pronounced increase in 2-deoxyglucose uptake distinguishes MΦLPS from MΦIFN-γ+TNF-α, MΦIL-4, and unstimulated macrophages (MΦ0 ). Despite having comparable levels of 2-deoxyglucose accumulation, MΦIL-4 can be distinguished from both MΦIFN-γ+TNF-α and MΦ0 based on the enhanced glutamine accumulation, which was associated with increased expression of a glutamine transporter, Slc1a5 . Ex vivo autoradiography experiments demonstrated distinct and heterogenous patterns of 18 F-fluorodeoxyglucose and 14 C-glutamine accumulation in atherosclerotic lesions of low-density lipoprotein receptor-null mice fed a high-fat diet. Conclusions—: Combined assessment of glutamine and 2-deoxyglucose accumulation improves the ex vivo identification of macrophage activation states. Combined ex vivo metabolic imaging demonstrates heterogenous and distinct patterns of substrate accumulation in atherosclerotic lesions. Further studies are required to define the in vivo significance of glutamine uptake in atherosclerosis and its potential application in identification of vulnerable plaques. Abstract : Supplemental Digital Content is available in the text.